Mask-Related Glasses Fogging: A Predisposing Mechanism of Falls during the COVID-19 Pandemic - John F. Dankert; Mandeep S. Virk (Case Reports in Orthopedics)
Fogging is a relatively infrequent, yet annoying, issue encountered by individuals who wear glasses. With the arrival of COVID-19, glasses fogging is more common due to the ubiquitous use of face masks. Individuals are stuck wrestling between leaving their mask off or trying to navigate their day-to-day lives with fogged glasses and risk falling. We report a case of an olecranon fracture sustained due to reduced visibility secondary to mask-related fogging during the COVID-19 pandemic. The recommendations included here will provide health care providers with the necessary information to educate patients regarding prevention of mask-related glass fogging.